2021
DOI: 10.1177/21582440211023202
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Korean version of the Wong and Law Emotional Intelligence Scale for Nurses

Abstract: Emotional intelligence is a social ability that enables one to control one’s emotions and understand and empathize with others, which is an essential skill for medical professionals, including nurses. However, no valid and reliable instrument exists to assess the emotional intelligence of nurses in Korea. Thus, the aim of this study was to evaluate the validity and reliability of the Korean version of the Wong and Law Emotional Intelligence Scale. To do this, the existing English version of the scale was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Item discrimination analyzed using the item–rest polyserial correlation, showed that all items had a good discriminative capacity, that is, they differentiated between people with low and high scores on the test, considering all items as a whole, as well as each group of items in their corresponding factor. These results coincide with those found in South Korea in a sample of nurses, where the item–rest correlations were greater than 0.40 ( Park and Yu 2021 ), and with those reported in Peru, in a sample of nursing students ( Carvalho et al 2016 ). On the other hand, in the analysis of the response options, it was observed that few people marked the lowest alternatives: even in the SEA_2 and UOE_4 items, no person selected the option “strongly disagree”.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Item discrimination analyzed using the item–rest polyserial correlation, showed that all items had a good discriminative capacity, that is, they differentiated between people with low and high scores on the test, considering all items as a whole, as well as each group of items in their corresponding factor. These results coincide with those found in South Korea in a sample of nurses, where the item–rest correlations were greater than 0.40 ( Park and Yu 2021 ), and with those reported in Peru, in a sample of nursing students ( Carvalho et al 2016 ). On the other hand, in the analysis of the response options, it was observed that few people marked the lowest alternatives: even in the SEA_2 and UOE_4 items, no person selected the option “strongly disagree”.…”
Section: Discussionsupporting
confidence: 90%
“…In a sample of South Korean nurses, the WLEIS presented a four-factor related factor structure, good reliability levels (α between 0.88 and 0.92 at the factor level and 0.91 for the total scale), adequate levels of item discrimination (r itc > 0.40), and the absence of floor and ceiling effects ( Park and Yu 2021 ). In China, the WLEIS was validated in a sample of university students, using a version with five response options in a Likert format, which showed good fit indices for the four related factors model, the higher-order model, and the bifactor model; the latter was slightly better than the previous ones, while the reliability for the four specific factors and the general factor was good (α > 0.70) ( Di et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average variance is explained, and composite reliability of all three constructs of WLEIS and SWLS have met their criteria for validity. 2,8,9,[11][12][13][14][15][16][17][18] Further, the model fit of the measurement model of WLEIS and SWLS also met their criteria of model fit, which means model can be studied and applied in neuroscience. Since the past few years, satisfaction with life has become a critical issue in the hospitality industry; the findings of the current study might help this sector by applying these scales.…”
Section: Discussionmentioning
confidence: 99%
“…Although the perceived EI as measured by the WLEIS has been criticized because it is based on a self-report measurement, robust evidence has shown invariances between the self-rating in this questionnaire and other ratings ( Libbrecht et al, 2010 ). Despite being conceived within a Chinese cultural framework, the WLEIS is considered a reliable tool for measuring emotional intelligence, has shown good reliability and validity across many cultures ( Extremera Pacheco et al, 2019 ; Iliceto and Fino, 2017 ; LaPalme et al, 2016 ; Park and Yu, 2021 ) and good reliability and validity in Chinese youth ( Kong, 2017 ; Shi and Wang, 2007 ). The Cronbach's α in the current study was 0.967.…”
Section: Methodsmentioning
confidence: 99%